The Effect Of Social Support, Academic Support, And Creativity On Entrepreneurship Intentions Of The Students’ Department Of Management, The University Of Riau For 2017 - Hrp, Reza Rizkyan; Marzolina, Marzolina; Fitri, Kurniawaty; Novrianti, Dian Puspita (Program Pascasarjana, Universitas Riau, 2023)
Entrepreneurial intention means someone with the intention of starting a business will have better readiness and progress in the business being run than someone without the intention of starting a business. The purpose of this study was to determine the effect of social support, academic support, and creativity on the entrepreneurial intentions of students in the Management Study Program, Faculty of Economics and Business, Riau University. This type of research is called descriptive quantitative. The sample in this study amounted to 80 people. Data collection techniques with questionnaires The data analysis method uses multiple linear regression analysis techniques with the help of SPSS software version 20. The results of the tests that have been carried out show that simultaneously show that social support, academic support, and creativity have an influence on the entrepreneurial intentions of students in the Management Department, Faculty of Economics and Business, Riau University. The managerial implication in this study is that parents and friends can provide social support to students. FEB UNRI can provide academic support in the form of holding entrepreneurial events such as seminars and bazaars. Students further increase creativity in entrepreneurship by finding new ideas that are suitable for business in the future.